Discounting, Cognitive Inflexibility, and Antisocial Traits as Predictors of Adolescent Drug Involvement - Hernández, Laura; Mejía, Diana; Avila-Chauvet, Laurent (Frontiers in Psychology, 2021)
Cognitive impairments such as steep delay discounting have been correlated with substance related disorders. However, antisocial traits (AT), cognitive inflexibility (CI), and loss discounting have been barely considered despite having a high relationship with problematic-consume. This study aims to identify differences between the four types of drug involvement, evaluating two cognitive tasks and antisocial traits. Fifty-two adolescents from middle and high school, between 13 and 19 years, were assessed with a substance involvement test, four discounting tasks using $3000, a card sorting test, and antisocial screening. Discriminant analysis with simultaneous estimation and varimax rotation was carried out. Non-use had lower AT and area under the curve (AUC) in probabilistic losses than problematic-consume. Moderate-consume had smaller AUC in delay losses than experimental use, and smaller AUC in probabilistic gains than problematic-consume. Function one included both losses discounting, function two AT and CI, and function three probabilistic gains. The three functions explained 60.1% of the variance. Results show that non-use showed lower AT and more preference for larger and unlikely punishments than problematic-consume. In turn, moderate-consume presented more predilection for large and delay punishments than experimental use, and less risk-taking than problematic-consume. High preference for small and soon punishments, and for larger and unlikely punishments distinguished non-use and experimental use of moderate-consume and problematic-consume. High AT and low CI distinguished experimental use group of non-use. Risk-taking did not discriminate effectively moderate-consume of problematic-consume.